2013
DOI: 10.1001/jamaoto.2013.4505
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Emergency Department Visits Following Thyroid and Parathyroid Surgery

Abstract: Patients taking PPIs are 1.81 times more likely to require ED evaluation than those who are not taking PPIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
0
13
1
Order By: Relevance
“…Literature surrounding ED utilization have mainly focused on specific procedures, not HNS as a whole. One study reported ED utilization after thyroidectomy and parathyroidectomy to be 11.22%, with common causes being paresthesia and wound complications [ 23 ]. Within our cohort, we noted an ED utilization rate of 8.43%, with the most common cause due to pain.…”
Section: Discussionmentioning
confidence: 99%
“…Literature surrounding ED utilization have mainly focused on specific procedures, not HNS as a whole. One study reported ED utilization after thyroidectomy and parathyroidectomy to be 11.22%, with common causes being paresthesia and wound complications [ 23 ]. Within our cohort, we noted an ED utilization rate of 8.43%, with the most common cause due to pain.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative complications are a frequent reason for otolaryngology patients to present to the emergency department . Young et al reviewed 30dEDRs in patients who underwent thyroidectomy or parathyroidectomy. They reported a 30dEDR rate of 11% with the most common reasons including electrolyte abnormalities (48%), hypertension (13%), and dehydration (5%).…”
Section: Discussionmentioning
confidence: 99%
“…A recent national audit performed in England revealed a postthyroidectomy hypocalcemia rate of 25%, recurrent laryngeal nerve injury rate of 2.3%, and a readmission rate of 2.5%, 17 similar to our finding and those of 3 other studies. [18][19][20] Although previous studies have evaluated risk factors for readmission after cervical endocrine surgery, this study is the first to operationalize risk factors into an easy-to-use risk score. Initially, using a traditional multivariable logistic regression, we identified numerous predictive factors.…”
Section: Discussionmentioning
confidence: 99%